2020
DOI: 10.1063/1.5144923
|View full text |Cite
|
Sign up to set email alerts
|

New Cf-252 neutron source shielding design based Monte Carlo simulation using material combination

Abstract: Neutron shielding has been a worldwide concern for decades and appropriate methods in nuclear reactors and associated facilities for shielding have been developed. Light materials such as paraffin and water cannot be used in neutron radiography due to structural and fire concerns, and a material in the solid form is needed for effective neutron shielding. Therefore, the present study developed a new neutron shielding design for fixed industrial radiography facilities with solid structures based on material com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…5 , 6 , and 7 , the horizontal effective dose profiles around the DSRS package are displayed. From these figures, it is observed that the distance needed to reduce the effective dose rate up to the ALARA acceptable limit for the public area (2.5 μSv/h) is 84.30 cm 14 , 16 , 27 , 30 , 39 , 54 , 55 . However, it appears to be 108.00 cm on the graph displayed in Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…5 , 6 , and 7 , the horizontal effective dose profiles around the DSRS package are displayed. From these figures, it is observed that the distance needed to reduce the effective dose rate up to the ALARA acceptable limit for the public area (2.5 μSv/h) is 84.30 cm 14 , 16 , 27 , 30 , 39 , 54 , 55 . However, it appears to be 108.00 cm on the graph displayed in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Monte Carlo methods also named MC techniques are usually acknowledged as a group of computational algorithms based on the principle of repetition of random sampling to estimate unknown parameters and that use random number generators to solve problems that are stochastics in nature. MC methods are effective in modeling complex situations and problems with a high degree of freedom that cannot be analytically solved, by performing random numbers and random experiments associated with a specific probability density function 27 , 32 , 39 . The application of MC to neutron transport is one of the most appropriate means to evaluate neutron interaction in a medium since the neutron interaction with matter (or a medium) is a cross-section-dependent function.…”
Section: Monte Carlo Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiographic testing is a defect detection method which utilizes rays, such as gamma rays, neutron rays, and X-rays, to pass through dense materials, such as metal components, in order to determine, based on the degree of ray attenuation, whether there are cracks, pores, and other defects [ 35 , 36 , 37 , 38 , 39 ]. Nevertheless, this detection method is harmful to the human body [ 40 , 41 ], as well as expensive and inapplicable to on-line monitoring. On the other hand, metal magnetic powder inspection can locate defects on welded parts by measuring the variations in the magnetic field caused by the faulty parts [ 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%